Revealing the genetic diversity of Sumbawa endemic horse using microsatellite-based DNA fingerprint (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sukri A, Dewi IN, Primawati SB, Wangiyana IGAS, Muttaqin Z, Winaya A. 2022. Revealing the genetic diversity of Sumbawa endemic horse using microsatellite-based DNA fingerprint. Biodiversitas 23: 4153-4159. Sumbawa horse (Equus caballus) is a genetic resource that must be preserved. Sumbawa horses have a significant economic, social, and cultural role. Information on the genetic status of the Sumbawa horse is needed as a step in developing a long-term conservation strategy. Therefore, this study aims to reveal the genetic diversity of the Sumbawa endemic horse using a microsatellite-based DNA fingerprint. DNA isolation was conducted from horse blood samples. Blood samples were taken from two horse farms with 24 individual horses from two different populations, namely Lalar and Liang,West Sumbawa District, Indonesia. Blood was taken from the jugular vein and collected by a qualified veterinarian from the Faculty of Veterinary Medicine, Universitas Pendidikan Mandalika. A total of 4 microsatellite primers were used in this study, INRA032, HEL09, CA425, and AHT4. This study revealed that the genetic diversity of horses in the Lalar population was higher than Liang. A greater number of alleles reinforces this; higher number and frequency of bands; and the presence of specific bands that indicate unique alleles. This research shows that the Sumbawa horse is unique from other horse breeds in the world. This is evidenced by the lower number of alleles per locus (Na) with a maximum number of two alleles per locus. Sumbawa horses have higher observed heterozygosity (Ho) than expected heterozygosity (He), with a Ho value less than 0.5. Analysis of Molecular Variance result has shown that variation within the population was higher than among the population. This is presumably due to the high gene flow in both horse populations caused by inbreeding. In general, AHT4 primers had the best ability to reveal the genetic diversity of Sumbawa horses with the highest Shannon's information index compared to other markers.